Stacked body and method for manufacturing the same

CN119212868BActive Publication Date: 2026-10-23DEXERIALS CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380041297.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-06-08
Filing Date
2023-05-25
Publication Date
2026-10-23
Estimated Expiration
2043-05-25

AI Technical Summary

Technical Problem

[0003]如果作为这样的导热材料使用金属或陶瓷,则具有不易轻量化,加工性差,或柔软性变低这样的问题

Benefits of technology

[0035]根据本发明,能够解决以往的上述各个问题,达成上述目的,能够提供能够实现高导热性和低热电阻的层叠体和层叠体的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212868B_ABST
    Figure CN119212868B_ABST
Patent Text Reader

Abstract

Provided is a laminate having: a substrate; a first heat-conductive layer containing a curing component, a curing agent that cures the curing component, first heat-conductive particles, and low-melting-point metal particles on the substrate; and a second heat-conductive layer containing a curing component, a curing agent that cures the curing component, second heat-conductive particles, and low-melting-point metal particles on the first heat-conductive layer, a part of the first heat-conductive particles contained in the first heat-conductive layer being in contact with a part of the second heat-conductive particles contained in the second heat-conductive layer, the volume average particle diameter of the first heat-conductive particles being smaller than the volume average particle diameter of the second heat-conductive particles, and the substrate containing at least one selected from the group consisting of silicon, aluminum, tungsten, molybdenum, glass, a molded resin, stainless steel, and ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to laminates and methods for manufacturing laminates. Background Technology

[0002] In various electronic devices, such as light-sensitive integrated circuits (LSIs), prolonged exposure to high temperatures due to the heat generated by the components used can lead to malfunctions and breakdowns. Therefore, thermally conductive materials are widely used to prevent LSIs from overheating. These materials prevent the device from overheating by diffusing or conducting the heat generated by the components to heat-dissipating components that release it to the atmosphere or other external components.

[0003] If metals or ceramics are used as such thermal conductive materials, problems arise such as difficulty in achieving lightweight properties, poor processability, or reduced flexibility. Therefore, various thermal conductive materials using polymers formed from resins or rubbers as the base material have been proposed.

[0004] For example, a thermally conductive adhesive has been proposed comprising a thermosetting adhesive containing a curing component and a curing agent for the curing component, and a metal filler dispersed in the thermosetting adhesive, the metal filler comprising silver powder and solder powder, the solder powder exhibiting a melting temperature lower than the thermosetting treatment temperature of the thermally conductive adhesive, and reacting with the silver powder under the thermosetting treatment conditions of the thermosetting adhesive to generate a high-melting-point solder alloy exhibiting a melting point higher than the melting temperature of the solder powder, the curing agent being a curing agent having flux activity for the metal filler, the curing component being a glycidyl ether type epoxy resin, and the curing agent being a tricarboxylic acid monoanhydride (for example, see Patent Document 1).

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent No. 5796242 Summary of the Invention

[0008] The problem that the invention aims to solve

[0009] However, in the prior art described in the aforementioned Patent Document 1, if a thermally conductive layer formed by a thermally conductive adhesive is formed between the copper substrate and the silicon substrate, the contact resistance at the silicon interface increases, resulting in a decrease in thermal conductivity.

[0010] The objective of this invention is to solve the aforementioned problems and achieve the following objective: to provide a laminate capable of achieving high thermal conductivity and low thermal resistance, and a method for manufacturing the laminate.

[0011] Methods for solving problems

[0012] The method for solving the above-mentioned problem is as follows. That is,

[0013] <1> A laminated body, characterized in that it has:

[0014] Substrate;

[0015] On the aforementioned substrate, there is a first thermally conductive layer containing a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles; and

[0016] On the aforementioned first thermally conductive layer, there is a second thermally conductive layer containing a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles.

[0017] A portion of the first thermally conductive particles contained in the first thermally conductive layer comes into contact with a portion of the second thermally conductive particles contained in the second thermally conductive layer. The volume average particle size of the first thermally conductive particles is smaller than that of the second thermally conductive particles.

[0018] The aforementioned substrate comprises at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.

[0019] <2> According to the laminate described in <1> above, the ratio (A:B) of the volume average particle size A of the first thermally conductive particle to the volume average particle size B of the second thermally conductive particle is 1:2 to 1:50.

[0020] <3> According to the laminate described in <1> or <2> above, the volume average particle size of the first thermally conductive particle is 0.3 μm or more and 30 μm or less.

[0021] <4> In the laminate according to any one of <1> to <3> above, the volume average particle size of the second thermally conductive particle is more than 1 μm and less than 100 μm.

[0022] <5> In the laminate according to any one of <1> to <4> above, the first thermally conductive particle and the second thermally conductive particle are at least any one of copper particles, silver-coated particles and silver particles.

[0023] <6> The laminate according to any one of <1> to <5> above, wherein the low melting point metal particles comprise Sn and at least one selected from Bi, Ag, Cu and In.

[0024] <7> In the laminate according to any one of <1> to <6> above, the curing agent has flux activity relative to the first thermally conductive particle and the second thermally conductive particle.

[0025] <8> The laminate according to any one of <1> to <7> above, wherein the cured component is at least one of an ethylene oxide cyclic compound and an oxobutane compound.

[0026] <9> The laminate according to any one of <1> to <8> above has a third thermally conductive layer between the first thermally conductive layer and the second thermally conductive layer.

[0027] <10> According to the laminate described in <9> above, the third thermally conductive layer is a copper foil.

[0028] <11> The laminate according to any one of <1> to <10> above has a counter substrate on the second thermally conductive layer that is opposite to the substrate.

[0029] The aforementioned opposing substrate comprises at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.

[0030] <12> A method for manufacturing a laminate, characterized by comprising the following steps:

[0031] The first thermally conductive layer forming process, which forms a first thermally conductive layer containing a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles on the aforementioned substrate, and...

[0032] The second thermally conductive layer forming process involves forming a second thermally conductive layer on the aforementioned first thermally conductive layer, comprising a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles.

[0033] The aforementioned substrate comprises at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.

[0034] The effects of the invention

[0035] According to the present invention, the aforementioned problems can be solved and the above-mentioned objectives can be achieved, and a laminate capable of achieving high thermal conductivity and low thermal resistance and a method for manufacturing the laminate can be provided. Attached Figure Description

[0036] Figure 1 This is a schematic diagram illustrating an example of a laminated body according to the first embodiment.

[0037] Figure 2 This is a schematic diagram illustrating an example of a laminated body according to the second embodiment.

[0038] Figure 3 A schematic cross-sectional view showing an example of the heat-dissipating structure used in this invention. Detailed Implementation

[0039] (Layered structure)

[0040] The laminate of the present invention comprises: a substrate, a first thermally conductive layer and a second thermally conductive layer, preferably a third thermally conductive layer and an opposing substrate, and further comprises other components as needed.

[0041] In this invention, by having a first thermally conductive layer and a second thermally conductive layer sequentially on a substrate, a portion of the first thermally conductive particles contacting a portion of the second thermally conductive particles, wherein the volume average particle size of the first thermally conductive particles is smaller than the volume average particle size of the second thermally conductive particles, thermal conductivity can be significantly improved even for substrates with poor solder wettability formed from at least one of silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics, as the contact area increases.

[0042] <Substrate>

[0043] There are no particular restrictions on the shape, structure, size, and material of the aforementioned substrates; they can be selected appropriately according to the purpose.

[0044] Examples of the shape of the aforementioned substrate include, for example, a plate or sheet. Examples of the structure of the aforementioned substrate include a single-layer structure and a laminated structure. Examples of the size of the aforementioned substrate can be appropriately selected according to the application and other factors.

[0045] The substrate material is one that is not easily wetted by solder, and includes at least one material selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics. Examples of ceramics include aluminum nitride, silicon carbide, alumina, and gallium nitride. Examples of molding resins include epoxy resin, silicone resin, urethane resin, and acrylic resin.

[0046] There are no particular limitations on the average thickness of the aforementioned substrates, and they can be appropriately selected according to the purpose.

[0047] The aforementioned substrate can be the heat-generating element (electronic component) itself in the heat-generating structure.

[0048] <First thermal conductive layer>

[0049] The first thermally conductive layer is formed on the substrate, preferably in contact with the substrate. The first thermally conductive layer contains a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles, and may further contain other components as needed.

[0050] -Fixed components-

[0051] As the curing component, at least one of ethylene oxide cyclic compounds and oxobutane compounds is preferably used.

[0052] --Ethylene oxide cyclic compounds--

[0053] The aforementioned ethylene oxide ring compounds are compounds containing an ethylene oxide ring, such as epoxy resins.

[0054] There are no particular limitations on the epoxy resins mentioned above; they can be appropriately selected according to the purpose. Examples include glycidyl ether type epoxy resins, phenolic varnish type epoxy resins, cresolic varnish type epoxy resins, bisphenol A type epoxy resins, triphenol type epoxy resins, tetraphenol type epoxy resins, phenol-phthalimide type epoxy resins, naphthol-phthalimide type epoxy resins, phenol-naphthol type epoxy resins, phenol-dicyclopentadiene type epoxy resins, alicyclic epoxy resins, and aliphatic epoxy resins. One type can be used alone, or two or more types can be used in combination.

[0055] --Oxycyclic butane compounds--

[0056] The above-mentioned oxetane compounds are compounds containing oxetane groups, and can be aliphatic, alicyclic, or aromatic compounds.

[0057] The aforementioned oxetane compounds can be monofunctional oxetane compounds having only one oxetane alkyl group, or polyfunctional oxetane compounds having two or more oxetane alkyl groups.

[0058] There are no particular limitations on the aforementioned oxetane compounds, and appropriate selection can be made according to the purpose. Examples include 3,7-bis(3-oxetane)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetane-methoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetane-methoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetane-methoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetane-methyl) ether, triethylene glycol bis(3-ethyl-3-oxetane-methyl) ether, tetraethylene glycol bis(3-ethyl-3-oxetane-methyl) ether, and 1,4-bis(3-ethyl-3-oxetane-methyl)propane. 3-Oxetrazolylbutane, 1,6-bis(3-ethyl-3-oxetrazolylbutane), 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, phenylenediamine dioxetane, 4,4'-bis[(3-ethyl-3-oxetrazolyl)methoxymethyl]biphenyl (OXBP), etc. They can be used individually or in combination of two or more.

[0059] As the aforementioned oxetane compounds, commercially available products can be used. Examples of such commercially available products include, for instance, the "ARONE OXETANE (registered trademark)" series sold by Toa Synthetic Co., Ltd., and the "ETERNACOLL (registered trademark)" series sold by Ube Industries, Ltd.

[0060] Among the above-mentioned ethylene oxide cyclic compounds and oxetane compounds, glycidyl ether type epoxy resin, phenolic varnish type epoxy resin, cresol phenolic varnish type epoxy resin, phenol-dicyclopentadiene type epoxy resin, bisphenol A type epoxy resin, aliphatic epoxy resin, and 4,4'-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl (OXBP) are preferred.

[0061] The content of the above-mentioned curing components is not particularly limited and can be appropriately selected according to the purpose. It is preferably 0.5% by mass or more and 60% by mass or less relative to the total amount of the first thermally conductive layer.

[0062] -Curing agent-

[0063] Examples of curing agents corresponding to the curing components mentioned above include, for instance, addition-polymerizing curing agents such as anhydride-based curing agents, aliphatic amine-based curing agents, aromatic amine-based curing agents, phenol-based curing agents, and thiol-based curing agents, as well as catalytic curing agents such as imidazole. One of these can be used alone, or two or more can be used in combination. Among these, anhydride-based curing agents are preferred.

[0064] When the curing component of the above-mentioned anhydride-based curing agent is epoxy resin, no gas is generated during heat curing, and a long shelf life can be achieved when mixed with epoxy resin. Furthermore, it is preferred from the perspective of achieving a good balance between the electrical, chemical and mechanical properties of the resulting cured product.

[0065] Examples of anhydride-based curing agents include, for example, cyclohexane-1,2-dicarboxylic anhydride and monocarboxylic acid anhydrides. Examples of monocarboxylic acid anhydrides include, for example, cyclohexane-1,2,4-tricarboxylic acid-1,2-anhydride.

[0066] The aforementioned curing agent exhibits flux activity, which is preferred from the perspective of improving the wettability of molten low-melting-point metal particles relative to thermally conductive particles. Examples of methods for the curing agent to exhibit flux activity include, for instance, introducing proton acid groups such as carboxyl groups, sulfonyl groups, and phosphate groups into the curing agent using known methods. Among these, introducing carboxyl groups is preferred from the perspective of reactivity with epoxy resins or oxobutane compounds that are curing components; examples include organic acids containing carboxyl groups such as glutaric acid and succinic acid. Furthermore, compounds modified from glutaric anhydride or succinic anhydride, or metal salts of organic acids such as silver glutarate, can also be used.

[0067] The content of the curing agent is not particularly limited and can be appropriately selected according to the purpose. It is preferably 0.1% by mass or more and 30% by mass or less relative to the total amount of the first thermally conductive layer.

[0068] The molar equivalent ratio (C / D) of the curing component C to the curing agent D varies depending on the type of curing component and curing agent used, and cannot be specified in general terms. It is preferably 0.5 to 3, more preferably 0.5 to 2, and even more preferably 0.7 to 1.5.

[0069] If the above equivalent ratio (C / D) is 0.5 or more and 3 or less, it has the advantage that when the thermally conductive composition is thermosetting, the low melting point metal particles can be fully melted and form a network.

[0070] -First thermally conductive particle-

[0071] The first thermally conductive particle is preferably any one of copper particles, silver-coated particles, and silver particles.

[0072] Examples of silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles.

[0073] The shape of the first heat-conducting particle is not particularly limited and can be appropriately selected according to the purpose. Examples include spherical, flat, granular, and needle-shaped particles.

[0074] The volume average particle size of the first thermally conductive particle is preferably 0.3 μm to 30 μm, more preferably 0.5 μm to 10 μm. If the volume average particle size of the thermally conductive particle is 0.3 μm to 30 μm, the volume ratio of the first thermally conductive particle to the low-melting-point metal particle can be increased, achieving high thermal conductivity and low thermal resistance. The volume average particle size can be measured, for example, by laser diffraction or a random particle size distribution measuring device (product name: Microtrac MT3300EXII).

[0075] -Low melting point metal particles-

[0076] For the aforementioned low-melting-point metal particles, the solder particles specified in JIS Z3282-1999 are suitable.

[0077] Examples of solder particles include, for instance, Sn-Pb-based solder particles, Pb-Sn-Sb-based solder particles, Sn-Sb-based solder particles, Sn-Pb-Bi-based solder particles, Sn-Bi-Ag-based solder particles, Sn-Cu-based solder particles, Sn-Pb-Cu-based solder particles, Sn-In-based solder particles, Sn-Ag-based solder particles, Sn-Pb-Ag-based solder particles, Pb-Ag-based solder particles, and Sn-Ag-Cu-based solder particles. One type may be used alone, or two or more types may be used together. Among these, solder particles containing Sn and at least one selected from Bi, Ag, Cu, and In are preferred, and Sn-Bi-based solder particles, Sn-Bi-Ag-based solder particles, Sn-Ag-Cu-based solder particles, and Sn-In-based solder particles are more preferred.

[0078] There are no particular restrictions on the shape of the aforementioned low-melting-point metal particles; they can be appropriately selected according to the purpose. Examples include spherical, flat, granular, and needle-shaped particles.

[0079] The melting point of the aforementioned low-melting-point metal particles is preferably 100°C to 250°C, and more preferably 120°C to 200°C.

[0080] The melting point of the aforementioned low-melting-point metal particles is lower than the thermosetting temperature of the aforementioned first thermally conductive composition. It is preferable that the molten low-melting-point metal particles can form a network (a continuous phase of metal) through the first thermally conductive particles in the cured product of the first thermally conductive composition, which can achieve high thermal conductivity and low thermal resistance.

[0081] The aforementioned low-melting-point metal particles react with the aforementioned thermally conductive particles under the thermosetting treatment conditions of the first thermally conductive composition to form an alloy exhibiting a higher melting point compared to the aforementioned low-melting-point metal particles, thereby preventing melting at high temperatures and improving reliability. Furthermore, the heat resistance of the cured product of the first thermally conductive composition is improved.

[0082] The heat curing treatment of the first thermally conductive composition described above is, for example, carried out at a temperature of 150°C or higher and 200°C for 30 minutes or more and 2 hours or less.

[0083] The volume average particle size of the aforementioned low-melting-point metal particles is preferably 10 μm or less, more preferably 1 μm or more and 5 μm or less. If the volume average particle size of the low-melting-point metal particles is 10 μm or less, the volume ratio of the low-melting-point metal particles to the heat-conducting particles can be reduced, thereby achieving high thermal conductivity and low thermal resistance in the first heat-conducting layer. The volume average particle size of the aforementioned low-melting-point metal particles can be measured in the same manner as the volume average particle size of the aforementioned first heat-conducting particles.

[0084] The volume average particle size of the first thermally conductive particle is larger than that of the low-melting-point metal particle. The volume average particle size ratio (A / B) of the thermally conductive particle A to the low-melting-point metal particle B is preferably 2 or more, more preferably 3 or more, and even more preferably 5 or more. The upper limit of the volume average particle size ratio (A / B) is preferably 20 or less, more preferably 10 or less.

[0085] By using low-melting-point metal particles with a smaller volume average particle size compared to the first thermally conductive particles, the thermally conductive particles become the main component in the first thermally conductive composition. The low-melting-point metal particles that exist between the first thermally conductive particles melt due to heating and alloy with the first thermally conductive particles to form a network, thereby achieving high thermal conductivity and low thermal resistance.

[0086] The volume ratio (A / B) of the first thermally conductive particle A to the low-melting-point metal particle B in the first thermally conductive layer is preferably 1 or more, more preferably 1.5 or more, and even more preferably 2 or more. The upper limit of the volume ratio (A / B) is preferably 5 or less, more preferably 4 or less, and even more preferably 3 or less.

[0087] If the volume ratio (A / B) is 1 or higher, the proportion of thermally conductive particles with larger volume average particle size compared to low-melting-point metal particles increases, thus suppressing the flow of molten low-melting-point metal particles. Furthermore, low-melting-point metal particles are less prone to separation even at interfaces that are not easily wetted (e.g., silicon), thus suppressing the influence of the interface material and improving the selectivity of the interface material.

[0088] -polymer-

[0089] The first thermally conductive layer preferably contains a polymer to impart flexibility, etc.

[0090] There are no particular limitations on the polymers mentioned above, and they can be appropriately selected according to the purpose. Examples include polymers that have at least one structure selected from polybutadiene, polysiloxane, poly(meth)acrylate, polyalkylene, polyalkyleneoxy, polyisoprene, polyisobutylene, polyamide, and polycarbonate within the molecule.

[0091] The content of the polymer relative to the total amount of the first thermally conductive layer is preferably 1% to 50% by mass, more preferably 1% to 30% by mass, and even more preferably 1% to 10% by mass.

[0092] -Other ingredients-

[0093] The first thermally conductive layer described above may contain other components as long as it does not impair the effect of the present invention. There are no particular limitations on the other components mentioned above, and they can be appropriately selected according to the purpose. Examples include thermally conductive particles other than metals (e.g., aluminum nitride, alumina, carbon fiber, etc.) and additives (e.g., antioxidants, ultraviolet absorbers, curing accelerators, silane coupling agents, leveling agents, flame retardants, etc.).

[0094] The first thermally conductive composition can be prepared by uniformly mixing the above-mentioned curing components, the above-mentioned curing agent, the above-mentioned first thermally conductive particles, the above-mentioned low-melting-point particles, the above-mentioned polymer, and other components as needed using conventional methods.

[0095] The average thickness of the first thermally conductive layer is not particularly limited and can be appropriately selected according to the purpose. It is preferably 1 μm or more and 100 μm or less, and more preferably 5 μm or more and 50 μm or less.

[0096] <Second thermal conductive layer>

[0097] The second thermally conductive layer contains a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles, and may further contain other components as needed.

[0098] -Second thermally conductive particle-

[0099] The second heat-conducting particle is preferably any one of copper particles, silver-coated particles, and silver particles.

[0100] Examples of silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles.

[0101] The shape of the second heat-conducting particle is not particularly limited and can be appropriately selected according to the purpose. Examples include spherical, flat, granular, and needle-shaped particles.

[0102] It is necessary that a portion of the first thermally conductive particles contained in the first thermally conductive layer are in contact with a portion of the second thermally conductive particles contained in the second thermally conductive layer, wherein the volume average particle size of the first thermally conductive particles is smaller than the volume average particle size of the second thermally conductive particles. If the volume average particle size of the first thermally conductive particles is larger than the volume average particle size of the second thermally conductive particles, the thermal conductivity of the laminate may sometimes decrease.

[0103] The ratio (A:B) of the volume average particle size A of the first thermally conductive particle to the volume average particle size B of the second thermally conductive particle is preferably 1:2 to 1:50, more preferably 1:10 to 1:40.

[0104] The volume average particle size of the second thermally conductive particle is preferably 1 μm to 100 μm, more preferably 10 μm to 70 μm, and even more preferably 10 μm to 50 μm. If the volume average particle size of the second thermally conductive particle is 1 μm to 100 μm, high thermal conductivity and low thermal resistance can be achieved. The volume average particle size of the second thermally conductive particle can be measured in the same manner as the volume average particle size of the first thermally conductive particle.

[0105] The curing components, curing agents, low-melting-point metal particles, polymers and other components in the second thermal conductive layer are the same as those in the first thermal conductive layer, so their details are omitted.

[0106] The average thickness of the second thermally conductive layer is not particularly limited and can be appropriately selected according to the purpose. It is preferably 20μm or more and 300μm or less, and more preferably 50μm or more and 200μm or less.

[0107] <Third thermal conductive layer>

[0108] The third thermally conductive layer is formed between the first thermally conductive layer and the second thermally conductive layer. The third thermally conductive layer can be a single layer or a plurality of layers, which may be two or more.

[0109] The third thermally conductive layer is preferably made of copper foil, considering its thermal conductivity.

[0110] The average thickness of the third thermally conductive layer is not particularly limited and can be appropriately selected according to the purpose. It is preferably 5μm or more and 200μm or less, and more preferably 10μm or more and 100μm or less.

[0111] <Opposite substrate>

[0112] The aforementioned opposing substrates are arranged opposite each other, and there are no particular restrictions on their shape, structure, size, material, etc., and they can be appropriately selected according to the purpose.

[0113] Examples of the shape of the aforementioned opposing substrate include, for example, a plate or sheet. Examples of the structure of the aforementioned opposing substrate include a single-layer structure or a laminated structure. The size of the aforementioned opposing substrate can be appropriately selected according to the application and other factors.

[0114] The aforementioned opposing substrate is made of a material that is easily wetted by solder, including at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof.

[0115] There are no particular limitations on the average thickness of the aforementioned opposing substrates, which can be appropriately selected according to the purpose.

[0116] The aforementioned opposing substrate can be the heat dissipation module itself in the heat dissipation structure.

[0117] <Other Components>

[0118] As for other components, there are no particular restrictions, and they can be appropriately selected according to the purpose. Examples include protective layers.

[0119] (Manufacturing method of laminated bodies)

[0120] The method for manufacturing the laminate of the present invention includes a first thermally conductive layer forming step and a second thermally conductive layer forming step, and may further include other steps as needed.

[0121] <First thermal conductive layer formation process>

[0122] The first thermally conductive layer forming process is a process of forming a first thermally conductive layer containing a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles on the above-mentioned substrate.

[0123] The aforementioned substrate comprises at least one selected from silicon, aluminum, tungsten, molybdenum, glass, molding resin, stainless steel, and ceramics.

[0124] The curing components, curing agents, first thermally conductive particles, and low-melting-point metal particles mentioned above are the same as those contained in the first thermally conductive layer, therefore their descriptions are omitted.

[0125] Examples of methods for forming the first thermally conductive layer include (1) applying a first thermally conductive composition containing a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles to a substrate and curing it; and (2) forming a cured layer on a support with a release layer, comprising a cured composition containing a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles, and transferring the cured layer onto the substrate. In (2) above, the support is peeled off when the cured layer is transferred onto the substrate.

[0126] Examples of methods for applying the first thermally conductive composition to the substrate as described in (1) include inkjet printing, blade coating, gravure coating, gravure offset coating, bar coating, roller coating, knife coating, air knife coating, comma coating, U-comma coating, AKKU coating, smooth coating, micro-gravure coating, reverse roller coating, 4-roller coating, 5-roller coating, dip coating, curtain coating, sliding coating, and mold coating.

[0127] <Second thermal conductive layer formation process>

[0128] The second thermal conductive layer forming process is a process of forming a second thermal conductive layer containing a curing component, a curing agent for curing the curing component, second thermal conductive particles, and low-melting-point metal particles on the first thermal conductive layer.

[0129] The curing components, curing agents, second thermally conductive particles, and low-melting-point metal particles described above are the same as those contained in the second thermally conductive layer, and therefore their descriptions are omitted.

[0130] Examples of methods for forming the second thermally conductive layer include (1) applying a second thermally conductive composition containing a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles to a first thermally conductive layer and curing it; and (2) forming a cured layer on a support with a release layer, comprising a cured composition containing a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles, and transferring the cured layer onto the first thermally conductive layer. In (2) above, the support is peeled off when the cured layer is transferred onto the first thermally conductive layer.

[0131] Examples of methods for imparting the second thermally conductive composition to the first thermally conductive layer as described in (1) above include inkjet printing, scraper coating, gravure coating, gravure offset coating, bar coating, roller coating, knife coating, air knife coating, comma coating, U-comma coating, AKKU coating, smooth coating, micro-gravure coating, reverse roller coating, 4-roller coating, 5-roller coating, dip coating, curtain coating, sliding coating, and mold coating.

[0132] <Other Processes>

[0133] As for other processes, there are no particular restrictions, and they can be selected appropriately according to the purpose. For example, the process of forming the third heat-conducting layer can be cited.

[0134] Here, embodiments of the laminated body of the present invention will be described in detail with reference to the accompanying drawings. Furthermore, in each drawing, the same reference numerals are used for the same constituent parts, and repeated descriptions are sometimes omitted. In addition, the number, position, shape, etc., of the constituent members described below are not limited to this embodiment; preferred numbers, positions, shapes, etc., can be derived based on the implementation of the present invention.

[0135] <First Embodiment>

[0136] Figure 1 This is a schematic diagram illustrating an example of a laminated body according to the first embodiment. Figure 1In the laminate 10, a first thermally conductive layer 12 containing a first thermally conductive particle 15 is provided on the substrate 11, a second thermally conductive layer 13 containing a second thermally conductive particle 16 is provided on the first thermally conductive layer 12, and an opposing substrate 14 is provided on the second thermally conductive layer 13.

[0137] A portion of the first thermally conductive particles 15 contained in the first thermally conductive layer 12 comes into contact with a portion of the second thermally conductive particles 16 contained in the second thermally conductive layer 13, wherein the volume average particle size of the first thermally conductive particles 15 is smaller than the volume average particle size of the second thermally conductive particles 16.

[0138] <Second Implementation>

[0139] Figure 2 This is a schematic diagram illustrating an example of a laminated body according to the second embodiment. Figure 2 In the laminate 20, a first thermally conductive layer 12 containing a first thermally conductive particle 15 is provided on the substrate 11, a third thermally conductive layer 17 as a copper foil is provided on the first thermally conductive layer 12, a second thermally conductive layer 13 containing a second thermally conductive particle 16 is provided on the third thermally conductive layer 17, and an opposing substrate 14 is provided on the second thermally conductive layer 13.

[0140] A portion of the first thermally conductive particles 15 contained in the first thermally conductive layer 12 and a portion of the second thermally conductive particles 16 contained in the second thermally conductive layer 13 are in contact through the third thermally conductive layer 17, wherein the volume average particle size of the first thermally conductive particles 15 is smaller than the volume average particle size of the second thermally conductive particles 16.

[0141] The laminate of the present invention, for example, can be adapted to form a power LED module or power IC module by connecting a heat-dissipating substrate, an LED chip or an IC chip, to a heat sink, thereby filling the tiny gap between a heat source such as an LSI and a heat sink, where heat flows smoothly between the two.

[0142] Here, as a power LED module, there are modules with wire bonding implementation type and modules with flip chip implementation type; as a power IC module, there are modules with wire bonding implementation type.

[0143] The heat-generating structure used in this invention consists of a heating element, the laminate of this invention, and a heat-generating component.

[0144] There are no particular restrictions on the types of heat-generating components mentioned above; they can be selected appropriately according to the purpose. Examples include electronic components such as CPU (Central Processing Unit), MPU (Micro Processing Unit), and GPU (Graphics Processing Unit).

[0145] As for the aforementioned heat-releasing component, if it is a structure that releases heat emitted by electronic components (heat-generating elements), there are no particular restrictions, and it can be appropriately selected according to the purpose. Examples include heat dissipation modules, heat sinks, heat spreaders, heat pipes, etc.

[0146] The aforementioned heat dissipation module is a component used to efficiently conduct heat from the aforementioned electronic components to other components. There are no particular limitations on the material used for the heat dissipation module; it can be appropriately selected depending on the purpose. Examples include copper and aluminum. The aforementioned heat dissipation module is typically in the shape of a flat plate.

[0147] The aforementioned heat sink is a component used to dissipate heat from the aforementioned electronic components into the air. There are no particular limitations on the material of the heat sink; it can be appropriately selected depending on the purpose, and examples include copper and aluminum. The aforementioned heat sink, for example, has multiple fins. The aforementioned heat sink, for example, has a base and multiple fins arranged such that they extend in a non-parallel direction (e.g., an orthogonal direction) relative to one surface of the base.

[0148] The aforementioned heat dissipation module and heat sink are generally solid structures without internal space.

[0149] The aforementioned vapor chamber is a hollow structure. The internal space of the hollow structure is filled with a volatile liquid. Examples of vapor chambers include those with a hollow structure, such as those with a hollow heat dissipation module or a plate-shaped hollow structure with a hollow heat sink.

[0150] The aforementioned heat pipe is a hollow structure in the shape of a cylinder, a roughly cylindrical shape, or a flat cylindrical shape. The internal space of the aforementioned hollow structure is filled with a volatile liquid.

[0151] here, Figure 3 This is a schematic cross-sectional view showing an example of a semiconductor device as a heat-dissipating structure. The laminate 7 of the present invention dissipates heat emitted by electronic components 3, such as semiconductor modules. Figure 3 As shown, the main surface 2a, which is fixed to the heat dissipation module 2 and faces the electronic component 3, is held between the electronic component 3 and the heat dissipation module 2. Furthermore, the heat-conducting sheet 1 is held between the heat dissipation module 2 and the heat sink 5.

[0152] The heat dissipation module 2 is formed, for example, in the shape of a square plate, having a main surface 2a facing the electronic component 3, and a sidewall 2b erected along the outer periphery of the main surface 2a. A heat-conducting plate 1 is provided on the main surface 2a surrounded by the sidewall 2b, and a heat sink 5 is provided on the opposite side 2c of the main surface 2a via the heat-conducting plate 1. The higher the thermal conductivity of the heat dissipation module 2, the lower the thermal resistance, and the more efficiently it absorbs heat from the electronic component 3, such as the semiconductor assembly. For example, it can be formed using copper or aluminum, which have good thermal conductivity.

[0153] Electronic component 3, for example, is a semiconductor component such as a BGA, and is mounted on the wiring substrate 6. In addition, in the heat dissipation module 2, the front end face of the sidewall 2b is mounted on the wiring substrate 6, thereby surrounding the electronic component 3 at a predetermined distance through the sidewall 2b.

[0154] Furthermore, by providing the laminate 7 of the present invention on the main surface 2a of the heat dissipation module 2, the heat emitted by the electronic component 3 is absorbed, thereby forming a heat-dissipating component that is heated by the heat sink 5.

[0155] Example

[0156] The following describes embodiments of the present invention, but the present invention is not limited by these embodiments.

[0157] (Examples 1-5, Comparative Examples 1-3, and Reference Example 1)

[0158] <Modulation of thermally conductive compositions>

[0159] The compositions and contents listed in Tables 1 to 3 were uniformly mixed using a stirring device (Rentaro Boto, automatic rotary mixer, manufactured by THINKY Co., Ltd.) to prepare the first and second thermally conductive compositions. Furthermore, the contents of each component in Tables 1 to 3 are parts by mass.

[0160] <Formation of Layered Bodies>

[0161] Next, in Examples 1 to 5 and Comparative Example 3, according to Tables 1 to 3, a first thermally conductive composition was applied to a 30mm × 30mm × 2mm substrate (silicon). Then, a second thermally conductive composition was applied to the first thermally conductive layer. A 30mm × 30mm × 2mm opposing substrate (copper) was stacked on the second thermally conductive composition and heated at 150°C for 60 minutes to cure it, forming a laminate with a first thermally conductive layer having an average thickness of 10μm and a second thermally conductive layer having an average thickness of 70μm.

[0162] In Example 2, copper foil with an average thickness of 30 μm was used as the third thermal conductive layer.

[0163] In Reference Example 1 and Comparative Example 1, the first thermally conductive composition was not used. Otherwise, the laminate was formed in the same manner as in Examples 1 to 5 and Comparative Example 3. In Reference Example 1, a 30mm × 30mm × 2mm substrate (copper) was used instead of a 30mm × 30mm × 2mm substrate (silicon).

[0164] In Comparative Example 2, the second thermally conductive composition was not used. Otherwise, the same procedure as in Examples 1-5 and Comparative Example 3 was followed to form a laminate.

[0165] Next, the thermal resistance and thermal conductivity of the resulting laminates are evaluated as follows. The results are shown in Tables 1 to 3.

[0166] <Thermal Resistance>

[0167] For each obtained laminate, the thermal resistance (°C·cm) was measured according to the method of ASTM-D5470. 2 / W). The thermal resistance of the cured product is calculated by subtracting the thermal resistance of the substrate and the opposing substrate from the result. The thermal impedance (Kmm) is then calculated from the thermal resistance and the area of ​​the cured product. 2 / W).

[0168] Thermal conductivity

[0169] For each obtained laminate, the thermal resistance (°C·cm) was measured according to the method of ASTM-D5470. 2 / W). The thermal resistance of the cured product is calculated by subtracting the thermal resistance of the substrate and the opposing substrate from the result. The thermal conductivity (W / m·K) is obtained from the above thermal resistance and the thickness of the cured product. The thermal conductivity is evaluated by the following criteria.

[0170] Evaluation Criteria

[0171] ◎: Thermal conductivity above 15 W / m·K

[0172] 〇: Thermal conductivity is above 10 W / m·K and below 15 W / m·K

[0173] ×: Thermal conductivity less than 10 W / m·K

[0174] Table 1

[0175]

[0176] Table 2

[0177]

[0178] Table 3

[0179]

[0180] Details of each component in Tables 1 to 3 are as follows.

[0181] -Curved components-

[0182] *OXBP: Manufactured by Ube Industries, Ltd., 4,4'-bis[(3-ethyl-3-oxetane)methoxymethyl]biphenyl

[0183] -Curing agent-

[0184] *Polycarboxylic acid, synthetic product of Dexerials Co., Ltd.

[0185] -Low melting point metal particles (solder particles)-

[0186] *Sn 42 Bi 58 Manufactured by Mitsui Metals & Minerals Co., Ltd., volume average particle size Dv: 4μm, melting point 139℃

[0187] -First thermally conductive particle-

[0188] *First thermally conductive particle 1: Ag particle, manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 1 μm

[0189] *First thermally conductive particle 2: Ag-coated Cu particles, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., with a volume average particle size Dv of 5 μm.

[0190] *First thermally conductive particle 3: Ag-coated Cu particles, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., with a volume average particle size Dv of 40 μm.

[0191] -Second thermally conductive particle-

[0192] *Second thermally conductive particle 1: Ag-coated Cu particles, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., with a volume average particle size Dv of 40 μm.

[0193] *Second thermally conductive particle 2: Cu particles, manufactured by Fukuda Metal Foil Powder Industry Co., Ltd., with a volume average particle size Dv of 40 μm.

[0194] *Second thermally conductive particle 3: Ag particle, manufactured by DOWA Electronics Co., Ltd., volume average particle size Dv: 1 μm

[0195] -polymer-

[0196] *M1276: Manufactured by Arkema Corporation, a polyamide compound.

[0197] Industry availability

[0198] The laminate of the present invention, as a thermal interface material (TIM), can achieve high thermal conductivity and low thermal resistance, and is therefore suitable for, for example, use in the peripherals of various electrical devices such as CPUs, MPUs, power transistors, LEDs, and laser diodes, where temperature can adversely affect the efficiency and lifespan of component operation.

[0199] This application asserts priority based on Japan Patent Application No. 202-93004 filed with the Japan Patent Office on June 8, 2022, and incorporates all the contents set forth in that application.

[0200] Symbol Explanation

[0201] 1. Thermal conductive sheet

[0202] 2. Heat dissipation module

[0203] 2a Main face

[0204] 3. Heating element (electronic component)

[0205] 3a above

[0206] 5. Heat sink

[0207] 6 Wiring board

[0208] 7-layered body

[0209] 10-layer stack

[0210] 11 Substrate

[0211] 12 First thermal conductive layer

[0212] 13 Second thermal conductive layer

[0213] 14 Opposite substrates

[0214] 15 First thermally conductive particle

[0215] 16 Second thermally conductive particles

[0216] 17 Third thermal conductive layer

[0217] 20-layer stack

Claims

1. A laminated body, characterized in that, have: Substrate; On the substrate, there is a first thermally conductive layer containing a curing component, a curing agent for curing the curing component, first thermally conductive particles, and low-melting-point metal particles having a melting point of 100°C to 250°C; and The first thermally conductive layer contains a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles having a melting point of 100°C to 250°C. A portion of the first thermally conductive particles contained in the first thermally conductive layer comes into contact with a portion of the second thermally conductive particles contained in the second thermally conductive layer. The volume average particle size of the first thermally conductive particles is smaller than that of the second thermally conductive particles. The substrate is silicon. The second thermally conductive layer has a counter substrate opposite to the substrate, the counter substrate being copper. The ratio of the volume average particle size A of the first thermally conductive particle to the volume average particle size B of the second thermally conductive particle, A:B, is 1:2 to 1:

50.

2. The laminated body according to claim 1, The volume average particle size of the first thermally conductive particle is between 0.3 μm and 30 μm.

3. The laminated body according to claim 1, The volume average particle size of the second thermally conductive particle is between 1 μm and 100 μm.

4. The laminated body according to claim 1, The first thermally conductive particle and the second thermally conductive particle are at least any one of copper particles, silver-coated particles, and silver particles.

5. The laminated body according to claim 1, The low-melting-point metal particles comprise Sn and at least one selected from Bi, Ag, Cu, and In.

6. The laminated body according to claim 1, The curing agent has flux activity relative to the first thermally conductive particle and the second thermally conductive particle.

7. The laminated body according to claim 1, The curing component is at least one of an ethylene oxide cyclic compound and an oxobutane compound.

8. The laminated body according to claim 1, A third thermally conductive layer is provided between the first thermally conductive layer and the second thermally conductive layer.

9. The laminate according to claim 8, The third thermally conductive layer is copper foil.

10. The method for manufacturing the laminate according to claim 1, characterized in that, Includes the following processes: A first thermally conductive layer forming process in which a first thermally conductive layer containing a curing component, a curing agent for curing the curing component, a first thermally conductive particle and a low-melting-point metal particle is formed on a substrate. The process of forming a second thermally conductive layer on the first thermally conductive layer, comprising a curing component, a curing agent for curing the curing component, second thermally conductive particles, and low-melting-point metal particles, and the second thermally conductive layer forming a second thermally conductive layer thereon. The process of stacking opposing substrates on the second thermally conductive layer.

Citation Information

Patent Citations

  • Detector for defect of sheet-like substance

    JP1982096242A

  • Thermal interface material based on composite thermal-conduction network of low-melting-point metals and thermal-conduction particles, and preparation method of thermal interface material

    CN108912683A

  • Composite thermal interface materials, thermal interface components, and methods for making the same

    US20190092994A1